Ecosystem services in a biosphere reserve context: identification, mapping and valuation - Ntshane, Basane Claire (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
Despite their contribution to human well-being, ecosystem services (ES) are being destroyed by anthropogenic activities, taken for granted and often compromised during land use decision making. The question that often arises is, what value do ES have compared to other undertakings that are economically robust, such as mining? The vision of the Millenium Ecosystem Assessment (MA) was a world in which natural assets (including ES) are appreciated and integrated into decision-making. The biodiversity strategy of the Convention on Biological Diversity (CBD) also concerns the integration of natural assets into decision making. Responding to challenges facing ES and their mainstreaming into decision-making has been constrained by lack of data and requires new tools and approaches. Integrating natural assets into decision-making is very important for South Africa (SA), where ES have been a crucial part of human systems for decades, and also because of the country's commitment to the implementation of the CBD's biodiversity strategy. With the aim of incorporating ES into decision-making in an integrated way, this study was conducted in two biosphere reserves (BRs), Vhembe and Waterberg, in Limpopo Province, SA. The aims of the study were the identification, mapping and valuation of ES following an integrated approach. In order to achieve these aims, the study attempted to address four key objectives: (1) to assess and evaluate the status of mapping and valuation of ES in SA, (2) to identify and quantify ES and their indicators, (3) to investigate and analyse the impact of land use/cover (LU/LC) change to ES and (4) to conduct valuation of selected ES. Two separate literature reviews were undertaken to assess and evaluate the status of mapping and valuation of ES in SA, thus addressing study objective 1. Both reviews detected a significant research gap with regard to mapping and valuation of supporting services in SA. To identify ES and indicators provided by the two BRs and to assess the impact of LU/LC change and its effect on ES, a participatory scenario planning process was conducted under three different scenarios, namely ecological development, social development and economic development. It became clear that LU issues were diverse in nature and affected ES in a number of ways and that there were always trade-offs in the choice of LU. For example, yields of ES were best in the ecological development scenario and were affected negatively, together with agricultural commodity production, in the social development and economic development scenarios. A mapping exercise was undertaken to illustrate the spatial distribution of ES supply and demand, involving five ES and 15 indicators using existing datasets and the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) mapping tool, again addressing objective 2 of the study. Carbon storage and habitat quality were assessed, modelled and quantified and their values provided in biophysical terms using InVEST modelling tools, thus addressing objective 4 of the study. High quantities of carbon storage and high habitat quality were recorded in natural areas and low quantities were recorded in managed systems (cultivated, urban and plantation areas). InVEST was again applied to conduct an economic valuation of two provisioning ES, timber and firewood, by determining their net present values, attempting to address objective 4 of the study. Results revealed that, at 12% discount rate, the net present value (NPV) for timber production accounted for R23 317/ha in VBR and R57 304/ha in WBR. However, at lower discount rates (4 and 7%), the NPVs for timber were negative in VBR and positive in WBR. With regard to firewood production, the NPVs were negative against all three discount rates in both study areas. I conclude by proposing a four-step integrated approach that can aid the successful incorporation of ES into decision-making: (1) maintain a balance between the social, economic and ecological aspects when making decisions on ES, (2) strive for an evidence- based approach to decision-making (use quantities and values), (3) apply integrated approaches (methods and techniques) to quantification and valuation, and (4) communicate all steps along the way. The results of this study will serve as a baseline for integration of ES into decision-making in SA.
Keywords: Uncatalogued